(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The reaction of organomagnesium compounds with thiochromane series acyl derivatives was studied. As a result of the reaction, it was found that thiochroman acyl derivatives react with organomagnesium compounds like aliphatic and aromatic ketones and form the corresponding tertiary alcohols with high yield.